THE EFFECT OF ADDITIONAL PROTEIN HYDROLYSATE OF REBON SHRIMP (Acetes sp.) ON THE QUALITY OF BISCUIT - Slamed Nuryal; Suparmi Suparmi; Dahlia Dahlia (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
AbstrakThis study aims to determine the effect of adding rebon shrimp protein hydrolysate to the quality of biscuits given different protein hydrolysate concentrations, seen from the organoleptic parameters and proximate analysis. The method used in this research was experimental, namely adding protein hydrolysate of rebon shrimp to biscuits. The design used in this study was a non-factorial Completely Randomized Design (CRD) with 4 levels of treatment, namely without giving rebon shrimp protein hydrolysate (T0), 5% rebon shrimp protein hydrolysate (T1), 10% rebon shrimp protein hydrolysate (T2), and 15% rebon shrimp protein hydrolysate (T3) with 3 replications so that the number of experimental units was 12 units. The parameters observed were organoleptic and chemical analysis. The results showed that the addition of rebon shrimp protein hydrolysate to biscuits had a significant effect on the appearance, taste, moisture, protein and fat content but had no significant effect on aroma, texture and ash content. Biscuits with the addition of high-quality rebon shrimp protein hydrolysate namely in the T3 treatment (addition of 15% rebon shrimp protein hydrolysate), with attractive, intact and neat characteristics, neutral aroma and slight shrimp odor, delicious, savory, and strong shrimp taste, solid texture, compact and crunchy, and chemical quality has met the Indonesian National Standard with moisture, ash, protein, and fat content was 3.83%, 1.5%, 29.37%, and 16.57% respectively.Keywords: Biscuits, shrimp rebon, protein hydrolysate